Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.2174/1389203721666200617133903
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Stroke: Mechanism, In vivo Experimental Models Thereof, and Neuroprotective Agents

Abstract: Background: Stroke is one of the causes of death and disability globally. Brain attack is because of the acute presentation of stroke, which highlights the requirement for decisive action to treat it. Objective: The mechanism and in-vivo experimental models of stroke with various neuroprotective agents are highlighted in this review. Method: The damaging mechanisms may proceed by rapid nonspecific cell lysis (necrosis) or by active form of cell death (apoptosis or necroptosis), depending upon the duration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 106 publications
0
1
0
Order By: Relevance
“…c -Jun N-terminal kinase (JNK) signaling is involved in the pathogenesis of ischemic stroke, along with multiple different signaling pathways [ 5 ]. The activation of JNK is observed after global and focal cerebral ischemia (FCI) in rats and mice [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ], and various small-molecule JNK inhibitors have exhibited neuroprotective effects in animal models, including stroke [ 25 , 26 , 27 , 28 , 29 ]. Recently, we found that the specific JNK inhibitors IQ-1S and IQ-1L exhibited neuroprotective activity in mouse and rat models of FCI, and in a rat model of global cerebral ischemia [ 22 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…c -Jun N-terminal kinase (JNK) signaling is involved in the pathogenesis of ischemic stroke, along with multiple different signaling pathways [ 5 ]. The activation of JNK is observed after global and focal cerebral ischemia (FCI) in rats and mice [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ], and various small-molecule JNK inhibitors have exhibited neuroprotective effects in animal models, including stroke [ 25 , 26 , 27 , 28 , 29 ]. Recently, we found that the specific JNK inhibitors IQ-1S and IQ-1L exhibited neuroprotective activity in mouse and rat models of FCI, and in a rat model of global cerebral ischemia [ 22 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%